“Motivated Signs”: Some Reﬂections on Phonosemantics and Submorpheme Theory in the Context of Democritus’ and Epicurus’ Traditions - Zheltova, Elena; Zheltov, Alexander (Hyperboreus, 2019)
The article attempts to trace how the diﬀerence in approaches to the question of language origin in the Democritus’ and Epicurus’ traditions is reﬂected in modern linguistics. According to the monograph by Alexander Verlinsky (2006), Democritus insisted on the arbitrary connection between objects and words, while Epicurus insisted on a necessary correlation between them. At ﬁrst glance, Democritus’ tradition has ultimately won, being reﬂected in the ideas of Ferdinand de Saussure that remain of crucial importance for modern linguistics. If looking further, however, the research on motivation or iconicity of language sign is still quite alive, with a number of relevant studies. This paper argues that the majority of studies on the motivation of language signs still follow the Democritus’ tradition rather than Epicurus’ one. They tend to ﬁnd the motivation based on purely intralingual data rather than in the “world of denotata”, the works by Roman Jakobson being of especial importance in this sense. Jacobson oﬀered the idea of paradigmatically motivated signs that are segmentally smaller than morphemes, and this idea was further developed by Konstantin Pozdniakov and other linguists into the theory of submorphemic signs and submorphemic neutralizations. In support of this theory, this paper illustrates how the submorphemic level of the language can be used for the description of Latin personal pronouns.